Na brincadeira, me perdi!: Zambê e outras práticas musicais no ambiente familiar de seu Geraldo Cosme, em Cabaceira-RN - Costa, Jaildo Gurgel da (2011)
This paper presents the results from an ethnographic investigation about zambê and other musical practices present in Sir Geraldo Cosme s family. The empirical field is located in the community of Cabeceira, municipality of Tibau do Sul, in the state of Rio Grande do Norte. In this town, economy is based on shrimp, sugar production and tourism. On the cultural expressions area, manifestations like coco de roda and, mainly, zambê kind of group music and dance, with responsorial singing and percussion accompaniment, originated from oral tradition have been highlighted. This investigation aims to identify, analyze and discuss the nowadays musical practices of the family studied. For that, it is considered that the local sonorous scenery is tensioned by two different segments, however dialogical: oral tradition and popular music, both organically interlinked and broadly communed, whether the divulgation of the repertories from electronics in general or through the local musical performances. The investigation process included bibliographical and documental research, field research, focusing on participant observation of several performances situations, and also covered analysis of photos, audio and video produced and lived on spot, as well as outside there. However, it includes the analysis of oral history as one of the main tools to guide this research. It was verified, through investigations, that in that place there is a significant and diverse number of traditional (such as zambê) and popular (genres produced by media) musical practices. It was also noticed that zambê dance attends basically to external demand, through paid presentations, while popular music is lived internally, voluntarily, as a way of entertainment. Before so many different musical genres present and shared in the same space, by the same public, musicians and moments, it was concluded that the sonorous practices in their different expressions, with uses and functions particularly defined, in the familiar context studied, are capable to dialogue and present specificities of each musical practice.